GUNUNG IRENG MENUJU KAWASAN CAGAR ALAM GEOLOGI (KCAG) - Dina Tania; Sri Mulyaningsih; N.A.A.T Heriyadi; Suhartono (DHARMA BAKTI, 2021)
The potential of Mount Ireng is not only a beautiful romance on the face of the earth, butalso the geological peculiarity of the facies of ancient volcanic centers based on the volcanic and volcanic rocks spread over 7 (seven) clusters in the form of andesitic blocky lava, andesitic lava, massive andesitic lava and basaltic andesite lava cushions scattered in 7 (seven) clusters in the form of blocky andesitic lava, andesitic lava, massive andesitic lava and basaltic andesite lava cushions spread over 7 (seven) clusters in the form of blocky andesitic lava, andesitic lava lava, massive andesitic lava andesite dike with the presence of pyrite and sulfur minerals which are carried by andesitic breccias and agglomerates, besides being supported by tourism potential as the location of the best sunrise in Yogyakarta. This became the foundation taken by the Gunung Ireng Geotourism Academic Advisory Team from IST AKPRIND Yogyakarta in the form of submission of Mount Ireng to a Geological Nature Reserve (KCAG) in order to increase the development of sustainable community-based geotourism management concepts.Verification is carried out through geological observations by exploring 7 (seven) clusters from the top to the foot of Mount Ireng to verify 53 Assessment Matrices including Criteria, Comparisons, Classifications (Scientific Values, Education and Tourism), Threat of Damage / Risk of Degradationand Utilization Recommendations. Hope is Mount Ireng, in the Srumbung Hamlet, Pengkok Village, Patuk Subdistrict, Gunung Kidul Regency, Special Region of Yogyakarta, which is believed to be the Ancient Volcanic Center Faces can become a Geological Nature Reserve Area (KCAG).